Biomarkers in Overactive Bladder: A New Objective and Noninvasive Tool? - Tiago Antunes-Lopes; Sérgio Carvalho-Barros; Célia-Duarte Cruz; Francisco Cruz; Carlos Martins-Silva (Advances in Urology)
Overactive bladder syndrome (OAB) is a highly prevalent urinary dysfunction, with considerable economic and human costs. Clinical diagnosis of OAB is still based on subjective symptoms. A new accurate, objective and noninvasive test to diagnose OAB and assess therapeutic outcome is lacking. Recent studies in lower urinary tract (LUT) dysfunctions, particularly in OAB patients, indicate that urinary proteins (neurotrophins, prostaglandins, and cytokines), serum C reactive protein, and detrusor wall thickness are altered, and such changes could be used as biomarkers of the disease. Nowadays, increasing emphasis has been given to the role of urinary neurotrophins, namely nerve growth factor (NGF) and brain derived neurotrophic factor (BDNF), as key players in some urinary dysfunctions. Although recently considered to be a bladder dysfunction biomarker, urinary NGF presents low sensitivity and specificity. Preliminary results suggest that BDNF may serve as a more efficient biomarker. Even though we have to wait for future studies to confirm the potential role of NGF and BDNF as OAB biomarkers, it is already clear that neurotrophins will contribute to elucidate the physiopathological basis of OAB. Herein are reviewed the latest advances in this new and exciting field, the detection and clinical application of emerging OAB biomarkers.